Competitor Analysis in Egyptian Private Higher Education Sector - Ayoubi, Rami M.; Loutfi, Mohamed (International Higher Education, 2018)
In this article, the authors introduce the idea of competition in the private higher education sector in Egypt. There are 24 private universities competing for students in Egypt. Based on two criteria, quality and price, the authors classify private profit-oriented universities in Egypt into four categories. They conclude that the current Egyptian government is striving to establish more universities in the high quality–high price category.